ANALISIS PENGARUH EARNING PER SHARE (EPS), PRICE EARNING RATIO (PER), DAN PRICE BOOK VALUE (PBV) TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2018 – 2023 - Supriyadi, Holili; Adhani, Ida; Ayu Nur Aini, Nabilah (Accounting Research and Business Journal, 2025)
This research aims to examine the influence of Earning Per Share (EPS), Price Earning Ratio (PER),and Price Book Value (PBV) on share prices in food and beverage sub-sector companies listed on theIndonesia Stock Exchange (BEI) in 2018-2023 , with a purposive sampling method. The data analysistechnique uses panel data regression, the type of data used is secondary data sourced from thecompany's annual financial report. The method used in this research is a quantitative method with dataanalysis using multiple linear regression tests involving classical assumption tests, followed by partialsignificance using the t test and to find out simultaneously the f test with a significance level of 5%,correlation coefficient test and also the coefficient of determination test (R2). The research results showthat the multiple linear regression test has the equation Y = -908,117+ 12,110X1 + 42,284X2 +495,152X3. Partially, the EPS variable has a significant effect on stock prices with a significance of0.000, while the PER and PBV variables do not have a significant effect on stock prices with asignificance of more than 0.05. Meanwhile, simultaneously the variables EPS, PER, and PBV have asignificant influence on share prices with a significance of 0.000< 0.05. The projection ability of the three variables on stock prices is shown from the results of thecoefficient of determination test (R2) which has an Adjusted R Square value of 50.2%. The remaining49.8% is explained by other variables outside the research model.